2001
DOI: 10.1161/hh2001.097796
|View full text |Cite
|
Sign up to set email alerts
|

Aging Enhances the Sensitivity of Endothelial Cells Toward Apoptotic Stimuli

Abstract: Abstract-Advanced aging leads to impaired endothelial NO synthesis and enhanced endothelial cell apoptosis; therefore, we investigated the sensitivity of aged endothelial cells toward apoptotic stimuli and determined the role of NO. Human umbilical vein endothelial cells (HUVECs) were cultured until 14th passage. In aged cells, oxLDL and tumor necrosis factor-␣-induced apoptosis and caspase-3-like activity were significantly enhanced more than 3-fold compared with young cells (passage 3). Because NO contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
220
3
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(241 citation statements)
references
References 52 publications
16
220
3
2
Order By: Relevance
“…19,23,26 Our results show that staurosporine-induced reduction in eNOS activity was associated with caspasemediated cleavage of eNOS. Long-term (18-24 h) exposure of either eNOS-transfected COS-7 cells or BAECs to staurosporine resulted in a significant loss of eNOS protein and activity, an effect that was significantly reduced by caspase inhibitors.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…19,23,26 Our results show that staurosporine-induced reduction in eNOS activity was associated with caspasemediated cleavage of eNOS. Long-term (18-24 h) exposure of either eNOS-transfected COS-7 cells or BAECs to staurosporine resulted in a significant loss of eNOS protein and activity, an effect that was significantly reduced by caspase inhibitors.…”
Section: Discussionmentioning
confidence: 54%
“…[20][21][22][23][24][25] Diminished eNOS-catalyzed production of NO or its bioavailability leads to endothelial apoptosis, and it has been speculated that this is associated with enhanced susceptibility to endothelial dysfunction and atherosclerosis. [26][27][28] As NO inhibits apoptosis in endothelial cells, it is intriguing to speculate that caspase-mediated loss of eNOS-derived NO further activates the caspase cascade, thereby promoting the apoptotic process by removing an impediment to cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,33,39 The reduced expression of TNFR2/p75 associated with increasing age, coupled with postischemic increases in the systemic levels of TNF-␣, favors apoptosis in adult ECs, 39 which could subsequently lead to inhibition of angiogenesis. Suppression of TNF with soluble TNFR1/p55 was reported to accelerate angiogenesis via upregulation of VEGF receptor KDR/Flk-1.…”
Section: Goukassian Et Al Tnfr2/p75 and Neovascularization 759mentioning
confidence: 99%
“…For example, early work by one of us (RGAF) failed to show any elevation in spontaneous apoptosis rates in HUVECs cultured to senescence (although baseline apoptosis rates as measured by TUNEL were significantly higher than those seen in fibroblasts) (Kalashnik et al 2000). Later studies (Hoffmann et al 2001) demonstrated that late passage HUVECs were more sensitive to apoptosis induced by oxidized LDL or TNFα compared to early passage cells. Jeon and Boo (2013) have recently shown that upregulation of the Fas receptor at both the mRNA and protein level in senescent HUVECs probably underlies their enhanced potential to undergo programmed cell death.…”
Section: The Relationship Between Cell Senescence and Immune Ligand Ementioning
confidence: 99%